The Competitive Advantage in the Car Rental Industry in the United States: A Comparison Study Between the Three Major Car Rental Companies - Alnasif, Ali (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2025)
This paper articulates and examines the factors that lead to and sustain the competitive advantage in the US car rental industry. A quantitative approach was adopted to collect data from companies’ financial statements. Preliminary data analysis, descriptive analysis, visualization, and ANOVA were used to analyze the competitive advantage variables in the proposed research models. The study indicates that Avis has the highest market share and profit margin, while Enterprise excels in fleet size and research and development investments. Hertz, on the other hand, is struggling to establish a foothold in the competitive market. Continuous adaptation to market changes, technological disruptions, and sustainability trends is essential for these corporations to maintain their competitive edge. Overall, the findings of this research will help corporations re-formulate and implement effective organizational strategies to cope with the brutal competition in the car rental industry and other industries.